Amputations versus Salvage: Reconciling the Differences - Black, Cara K.; Ormiston, Laurel D.; Fan, Kenneth L.; Kotha, Vikas S.; Attinger, Christopher; Evans, Karen Kim (Journal of Reconstructive Microsurgery, 2019)
Background There are many factors to consider when choosing between amputations versus salvage in lower extremity reconstructive surgery. Postoperative functionality and survival benefit are critical factors when deciding between limb salvage and amputation.Methods In this review, we present the evidence and the risks and benefits between these two options in the setting of the acute, trauma population and the chronic, diabetes population.Results The trauma population is on average young without significant comorbidities and with robust vasculature and core strength for recovery. Therefore, these patients can often recover significant function with anamputation and prosthesis. Amputation can therefore be the more desirable in this patient population, especially in the case of complete traumatic disruption, unstable patients, high risk of extensive infection, and significant nerve injury. However, traumatic lower extremity reconstruction is also a viable option, especially in the case of young patients and those with intact plantar sensation and sufficient available tissue coverage. The diabetic population with lower extremity insult has on average a higher comorbidity profile and often lower core strength. These patients therefore often benefit most from reconstruction to preserve limb length and improve survival. However, amputation may be favored for diabetics that have no blood flow to the lower extremity, recalcitrant infection, high-risk comorbidities that preclude multiple operations, and those with end stage renal disease.Conclusion Many patient-specific factors should be considered when deciding between amputation vs. salvage in the lower extremity reconstruction population.
Keywords: lower extremity; salvage; amputation; free tissue transfer; free flap